A Linear Programming Analysis of Integrated Agriculture-Aquaculture Mixed Fanning - Alsagoff, Syed Kadir; Kuperan, K.; Ariff Hussein, Mohd (1992)
Aquaculture has the potential for contributing significantly towards enhancing farm income and hence towards solving the poverty problem among farm smallholders. This study attempts to evaluate the economics of mixed farming among sampled farmers in Central Perak and to assess the contribution of aquaculture to the overall farm income. Income from aquaculture was found to be substantial and has the potential for further increase if farm resources are allocated optimally or integrated agriculture with freshwater fish poly culture and broiler meat production can be implemented.